Topics on the theory of Frobenius manifolds - Castro, Thales Novelli (2024)
This work aims to present a connection between Frobenius manifolds, a concept of differential geometry which shows up in topological field theory, and systems of differential equations of hydrodynamic type. Formulated by Dubrovin in the 1990s, Frobenius manifolds aim to give a geometric interpretation to the so-called associativity equations, or WDVV equations, a nonlinear system whose solution is a quasi-homogeneous function describing structure constants of an associative algebra. Hydrodynamic-type systems arise, as the name suggests, in studies on fluid mechanics, especially gas dynamics. From the geometric approach, the relation between these two entities is given by means of a Hamiltonian representation for these equations, arising from a specific type of Poisson structure. Specifically, the work presents an overview of the main geometric aspects of the theory, leading to a theorem according to which the loop-space of a Frobenius manifold carries a so-called bi-Hamiltonian structure of hydrodynamic type.